Mengamati Akuntabilitas Pengelolaan Dana Desa Di Desa Kalikotes Klaten - Devy Anugrah Heni; Puji Wibowo (Akuntansiku, 2022)
Village funds are an issue that is often discussed in line with the policy of distributing village funds that are increasingly widespread. One of the debated issues is how well the village apparatus is able to use village funds in an accountable manner for the prosperity of the people in their village. This study aims to review the accountability practices of village fund management in Kalikotes Village, Kalikotes District, Klaten Regency. The village fund accountability observed was the period before the Covid-19 pandemic, namely 2015-2019. This study uses a mixed method, namely qualitative research with a case study approach which is complemented by survey-based research. Based on the results of interviews and distributing questionnaires, it was concluded that in principle the accountability of village fund management in Kalikotes Village has been going well. Issues that need to be addressed immediately are the competence of human resources and community participation. Community competence can be improved through regular technical training in village financial management. Meanwhile, community participation can be increased through the dissemination of information that is more open and reaches all levels of society.   Dana desa menjadi isu yang sering didiskusikan seiring dengan kebijakan penyaluran dana desa yang semakin luas. Salah satu persoalan yang diperdebatkan adalah seberapa baik para aparatur desa mampu memanfaatkan dana desa secara akuntabel demi kemakmuran rakyat di desanya. Penelitian ini bertujuan untuk melihat kembali praktik akuntabilitas pengelolaan dana desa di Desa Kalikotes, Kecamatan Kalikotes, Kabupaten Klaten. Akuntabilitas dana desa yang diamati adalah periode sebelum pandemi Covid-19 yaitu tahun 2015-2019. Penelitian ini menggunakan mixed method yaitu penelitian kualitatif dengan pendekatan studi kasus yang dilengkapi dengan riset berbasis survei.  Berdasarkan hasil wawancara dan penyebaran kuesioner yang dilakukan, diperoleh simpulan bahwa pada prinsipnya akuntabilitas pengelolaan dana desa di Desa Kalikotes telah berjalan dengan baik. Persoalan yang perlu segera dibenahi adalah kompetensi sumber daya manusia dan partisipasi masyarakat. Kompetensi masyarakat dapat ditingkatkan melalui pelatihan teknis pengelolaan keuangan desa secara rutin. Adapun partisipasi masyarakat dapat ditingkatkan melalui penyebaran informasi yang lebih terbuka dan menjangkau seluruh lapisan masyarakat.